An Empirical Analysis of Impact of E-commerce on Banking Industry in China - Jiang, Bo (2010)
In recent years, e-commerce grows rapidly in the whole world. In the United State and European countries, e-commerce has become a significant financial service channel and played an irreplaceable role comparing with traditional banking. In these ten years, the banking industry in China has begun to implement e-commerce in order to serve their customers better. The implementation of e-commerce has changed people’s understanding of financial issues. Meanwhile, e-commerce brings new profit point and profit mode for commercial banks. However, because of the difference of environment and condition in each bank, the impacts of e-commerce will also change. There are a great deal of researches has been done on how e-commerce affect the operations of manufacture industry. However, there are few studies concern the impact of e-commerce on banking industry in China and how e-commerce integrate operations processes and reduce operational costs for banking industry. The purpose of this study is to estimate how e-commerce has affected the capacity of bank to satisfy the customers’ needs and simplify the operation processes. This dissertation followed a grounded theory methodology which used interview with the participants from state-owned commercial bank, joint-stock commercial bank, local commercial bank and policy bank. Then, the dissertation discussed the results of the ten case study conducted in the China banking industry. The research showed that the significant positive impacts of e-commerce to banking industry in China is in operation cost, competitive advantage, customer satisfaction, operation processes, and customer relationship, while the significant negative impacts is in after-sales service, communication, marketing, and security. Based on the results of the case study, this dissertation also provide some rational suggests to the development of e-commerce in China banking industry in future.